The effects of the global financial crisis on the colombian local currency bonds prices : an event study (2016)
Purpose The purpose of this paper is to perform an event study using high frequency data on peso-denominated Colombian government bonds to measure the effects of news during the global financial crisis (GFC). Design/methodology/approach Using standard event study methodology, the authors want to see if a surprise (originating from macroeconomic news and GFC events) has a significant effect on asset prices measurable as abnormal returns. The authors also assume that the US market acted as a transmission mechanism for the crisis in a standard market model framework and control for confounding effects from events that originated from the crisis by taking into account the effect of global, regional and local macroeconomic surprises in the period before, during and after the GFC. Findings The results show that there was resilience and decoupling of the Colombian local currency bond market from the events of the GFC. Research limitations/implications The results show that there was resilience (in terms of abnormal returns) and decoupling of the Colombian local currency bond market from the events of the GFC. The paper also finds that, on an average, Colombian bonds performed better during the period of the GFC than the period before and after the GFC. Practical implications In the event study using individual bonds the paper finds that, in most cases, negative news had a positive impact in Colombian bond prices during the GFC. Social implications These results have important policy implications in emerging markets economies in terms of the benefits of substituting foreign currency debt with local currency debt. Originality/value This paper provides a date and time-specific timeline (Table III) of the most significant GFC events and news. The paper finds that for all the periods under observation local news related to inflation had the greatest impact in bond prices. In the case of global and regional news, inflation and trade-related surprises had also significant effects on bond prices but to a lesser extent.